General Elections India 2019: A Study Of Gurgaon Parliamentary Constituency In Haryana - Bhardwaj, Jai Kishan (International Journal of Psychosocial Rehabilitation, 2020)
There was Modi wave in India for the second time after Pulwama terrorist attack in Jammu and Kashmir, with the state of Haryana being no exception. After the agitation for Jat reservation, the political equation in Haryana changed as it mobilised the non-Jat voters in favour of BJP. In Gurgaon parliamentary constituency, the most developed district of Haryana Gurgaon and the most backward district of both Haryana and India Nuh (erstwhile Mewat) co-exist. Moreover, communities of Meo Muslims and Hindu Ahirs are dominant in the region. The present paper analyses the outcome of elections on economic and social considerations in this Parliamentary constituency of Haryana.